Nitrogen addition gradient can regulate the environmental filtering of soil potassium or phosphorus in shaping the community assembly of alpine meadow. (February 2020) - Li, Shuai; Dong, Shikui; Shen, Hao; Xu, Yudan; Gao, Xiaoxia; Han, Yuhui; Zhang, Jing; Yang, Mingyue; Li, Yu; Zhao, Zhenzhen; YunfengYang,; Liu, Shiliang; et al.
Graphical abstract: Highlights: No functional traits connected both phylogeny and environmental factors. N addition at 8 kg N ha -1 year −1 filtrated the species of the gramineae. N addition at 72 kg N ha −1 year −1 filtrated the species of non-gramineae. Potassium in normal year and phosphorus in warm year were main factors of environmental filtering. Abstract: Nitrogen (N) deposition and warming leads to environmental gradients that shape plant communities and ecological diversity, space is treated as an equally important variable as the environmental variables in the environmental gradients. The Qinghai-Tibetan Plateau (QTP) is very sensitive to large increases in N deposition rates and warming. Environmental gradients caused by N deposition and spatial factors act as environmental filtering in community assembly by affecting plant functional traits and phylogeny. To investigate the effects of environmental filtering caused by N deposition on the community assembly in alpine meadows, we randomly placed and fertilized at 6 levels of N addition (no N addition, 8 kg N ha -1 year −1, 24 kg N ha −1 year −1, 40 kg N ha −1 year −1, 56 kg N ha −1 year −1 and 72 kg N ha −1 year −1 ) both in a normal (normal precipitation and normal temperature) year and a warm (normal precipitation and warm) year. We used the fourth-corner analysis and extended RLQ (R stands for a matrix of environmental variables by samples, L stands for a species-cover-by-samples matrix and Q stands for a species-by-traits matrix) through multiple factors (soil factors, spatial heterogeneity, species traits, phylogenetic factor) to examine the effects of environmental filtering on the community assembly in alpine meadows. The results demonstrated that all soil variables showed a clear gradient and were affected by simulated N deposition; N addition at 8 kg N ha -1 year −1 can filtrate the species of the gramineae, but N addition at 72 kg N ha −1 year −1 can filtrate the species of non-gramineae, the main factors of environmental filtering were potassium in normal year and phosphorus in warm year. With the increase of N deposition rate in alpine meadow of QTP, non-gramineous plants will be favored first, but eventually gramineous plants will occupy the dominant position in the QTP. Rational mitigation strategies should be developed for different climate change scenarios of alpine grasslands on the QTP according to their responses to the N addition gradients and climate change scenarios in the future.